Exploring threshold effect of board size on firm value: Does size matter? - Yee-Ee Chia (Malaysian Finance Association, 2024)
Research Question: What is the threshold level of board size for the Malaysian stock market? Motivation: This study aims to determine the appropriate size of the board of directors for the Malaysian stock market. Idea: There is a non-monotonic relationship between board size and firm value which underlies two competing views on agency and resource dependence theories. Data: Firm characteristics and board governance data are collected from the Datastream and annual reports of Bursa Malaysia for the period 2000 – 2020 covering 1,247 firms listed on the Malaysian stock market. Method/Tools: This study uses a panel threshold estimation method to explore the nonlinearity of board size on firm value, together with a battery of robustness checks. Findings: The findings of a U-shaped curve imply that before the threshold point, having more directors on the board is associated with lower firm value due to higher agency costs. However, when the threshold point exceeds a certain level, the positive effect dominates, and the super-sized boards are associated with a higher firm value. The results show that the positive impact of board size on firm value begins only after the size of the board exceeds the 1.90 threshold level which is equivalent to 7 directors. Therefore, this paper shows that the number of outsider directors is the positive channel link to the board size-firm value relationship. Contributions: This study contributes to the finance literature by exploring the nonlinearity of board size and firm value based on agency and resource dependence theories. First, the evidence of the U-shaped relationship is consistent with the resource dependence theory prediction that super-sized boards delivered higher firm value. Second, firm value benefit will begin when the board size is more than 7 number of directors. Third, a comprehensive dataset covering 21 years period from 2000 – 2020, yielded a more precisely estimated regression that allows us to determine the long-term impact of Malaysia’s corporate governance board policies after a few rounds of amendments to the MCCG report. Fourth, a board with a greater number of outsider directors is the positive channel mechanism linked to board size and firm value.